“Prestenção”: o treinamento da atenção, na improvisação em dança e suas reverberações na composição e cena. - Oliveira, Larissa Abelardo de (2022)
This dissertation aims to analyze how attention is worked by groups and collectives of Improvisers in dance and how this reverberates in the compositional processes and in the scene. For this purpose we will try to explain the idea of Improvisation in dance, mainly about the concepts and procedures linked to the field of Real-Time Composition and Choreographic Game, as well as to approach the historical and aesthetic perspectives, presenting the main names of Contact Improvisation and Improvisation in dance since the 1960s until nowadays. This discussion is based on a bibliographical study of the topic and on interviews with artistic groups that are active in the field of dance improvisation in Brazil by means of questionnaires. This research is justified by the fact that it aims to broaden the study of dance improvisation processes and to analyze the attentional work in training, in the creation process and in the improvised scene. It seeks to answer the following question: How is the attentional work in dance improvisation used to enhance the work of groups and collectives in their composition processes and on stage? In this direction, this paper will present some ideas on how the development of attention has been worked by these groups, in order to contribute with the work done in improvisational practices, such as Choreographic Game, Improvised Scene or Real- Time Composition.